Association between religious practice and risk of depression in older people in the subacute setting. (20th March 2017) - Lac, Alice; Austin, Nicole; Lemke, Renata; Poojary, Suma; Hunter, Peter
Abstract : Objective: To identify the association between religious practice and risk of depression in older people admitted to a subacute hospital. Methods: A cross‐sectional survey was conducted with 100 patients aged ≥65 years with Mini‐Mental State Examination (MMSE) scores ≥24 consecutively admitted to a subacute hospital. Religious practice was measured using the Duke University Religion Index and risk of depression using the 15‐item Geriatric Depression Scale (GDS). Results: Geriatric Depression Scale was significantly correlated with intrinsic religiosity ( r = −0.21, P = 0.04) and cognition ( r = −0.22, P = 0.03). Conclusion: This cross‐sectional study of older people in a subacute setting found depression scores were negatively and independently associated with both intrinsic religiosity and cognition. In conjunction with cognitive assessment, health professionals working with older people may consider taking a spiritual history as part of holistic care.